(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Fistula-in-ano is one of the most difficult diseases confronted in ano-rectal patients in Shalyatantra OPD. Sushruta described Bhagandara along with its etiology, clinical presentation and treatment. The description of different types of Bhagandara (fistula-in-ano) are at par with the aetiopathogenesis of Fistula-in-ano of modern medical science. It is a very complicated condition arising out of various causes like pyogenic, tubercular, lymphogranuloma inguinale, inflammatory bowel diseases like Crohn’s disease, ulcerative colitis etc. Identification of the aetiopathological factor is necessary for the success of treatment of fistula-in-ano. Histopathological study of tissue from tract of fistula-in-ano is an useful diagnostic tool for assessing the underlying pathology. In this study we use the benefits of histopathological examination from the primary site of the disease to detect the basic etiology. 100 cases diagnosed as fistula-in-ano attending Shalya OPD, Government Ayurvedic College Hospital were randomly selected for a period of one year i.e 2016-2017. After necessary investigations, tissue is collected from the primary site of fistulous tract during primary threading for Kshar Sutra therapy, in OT under local anaesthesia and sent for histopathological examination. The results of the above study were tabulated and lots of cases other than pyogenic cause were detected. The data were analysed with standard statistical methods. Without histopathological examination it is not possible to detect the underlying cause of fistula-in-ano.